Density Decline in a Mediterranean Seahorse Population: Natural Fluctuations or New Emerging Threats? - Pierri, Cataldo; Cardone, Frine; Corriero, Giuseppe; Lazic, Tamara; Quattrocchi, Federico; Alabiso, Giorgio; Gristina, Michele (Frontiers in Marine Science, 2021)
Illegal wildlife trade is considered one of the most serious threats to biodiversity worldwide, along with habitat loss/degradation and overfishing of wild stocks. Seahorses are considered at high risk as these fish represent an important component of traditional Chinese medicine but are also sold as curios and ornamental fish. On a worldwide level, illegal trade is controlled by numerous laws and regulations, but it seems to continue by assuming more dynamic routes. In the Mediterranean Sea, Hippocampus guttulatus formed one of the largest populations at Mar Piccolo di Taranto in South-Eastern Italy. During the routine monitoring of this population in 2016, a dramatic density decrease was observed. By using questionnaires and long-term datasets, the present study determined possible causes of this decline by investigating habitat changes, temperature trends and the existence of seahorse trafficking while also examining abundance trends during the last decade. The results indicated a sharp density decline starting from 2015, co-occurring with the period of high temperatures, while habitats remained almost constant. However, interviews with main stakeholders described both illegal and legal fishing activities as the main drivers for the declining seahorse density. Indeed, at one of the studied sites, which was under strict military control, seahorse abundance started to decline only after the intensification of fishing pressure in the basin. The study suggests that Mar Piccolo di Taranto could be one of the sources for international seahorse trade, thus highlighting the need for more intense and effective actions to prevent and combat illegal poaching, while threatened populations are requiring continuous and close monitoring. Due to unfavourable socio-economic conditions, a viable and thriving seahorse population at Mar Piccolo di Taranto could contribute to the revitalization of the coastal economy and the development of environmental awareness.